The Effect of Board Independence on Information Asymmetry - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2016)
Boards have an important role in ensuring that investors’ interests are protected. Our paper first examines whether the independence of a firm's board affects information asymmetry among investors. We provide evidence that greater board independence leads to lower information asymmetry. Next, we provide evidence that more voluntary disclosure and greater analyst coverage are two underlying mechanisms via which greater board independence reduces information asymmetry. Of the two mechanisms, we find that analyst coverage is more significant in influencing how board independence affects information asymmetry. Overall, our paper contributes to a better understanding of the effect of board independence on information asymmetry.